Synthesis and Biological Evaluation of Some New Chalcone Derivatives as Anti-inflammatory Agents - Rehman, Zia U.; Saini, Pooja; Kumar, Sushil (Current Drug Discovery Technologies, 2023)
Aim: The present research work aims to prepare a series of 1-(4-(2-(1H-indol-1-yl)-2- oxoethoxy)phenyl)-3-phenylprop-2-en-1-one derivatives. Methods: The major compound was achieved by the reaction of indole with chloroacetylchloride in benzene afforded 2-chloro-1-(indoline-1-yl) ethanone which reacts o- hydroxy acetophenone in presence of acetonitrile to form 2-(4-acetylphenoxy)-1-(1H-indol-1-yl)ethan-1-one then goes through aldol condensation to give various final derivatives. Results and Conclusion: After the synthesis of compounds, the synthesized compounds were characterized by checking their solubility, melting point, thin layer chromatography, IR, 1HNMR spectral data and elemental analysis. All of the prepared derivatives were evaluated for their anti-inflammatory activity on wistar albino rats by following the carrageenan-induced Rat Hind Paw Edema model.
Keywords: substituted benzaldehyde